Propagation, planting density, and fertiliser types effect on the growth, leaf biomass, and phytonutrients of Moringa (Moringa oleifera L.) - Farahzety, Abdul Mutalib (2024)
Moringa (Moringa oleifera L.) is a rich source of phytonutrients for both humans and animals. However, a standardized method for propagating Moringa through cutting and seeds is lacking, thus limiting its widespread cultivation. Hence, studies were carried out to determine suitable treatments to produce high-quality propagation materials from cuttings and seeds, as well as the effects of plant densities and fertiliser types on leaf production and phytonutrients under local conditions. Laboratory and field studies were conducted to determine the optimal priming treatments and duration on germination and seedling growth of Moringa. The experiment was a completely randomised design (CRD), with four replicates for each treatment of hydropriming (water), osmopriming (KNO3) at 1% (w/v), and nutripriming (Humic acid and Trace Elements) at 1% (w/v) for 4, 8, and 12 hours. In a greenhouse study, the experiment examined the effects of priming treatments and growing media on Moringa seed emergence and seedling growth in a randomised completely block design (RCBD) with 3 replications. Subsequently, a study on vegetative propagation was carried out to investigate the influence of stem diameter, bio-stimulant, and growing media on the growth of Moringa cuttings. The experiment design was three factorials with three diameter classes, 20 mm (16-25 mm), 30 mm (26-35 mm), and 40 mm (36-45 mm), two growing media [sand: peat (9:1) and topsoil: coir dust: peat (5:2:1)] and biostimulant (Moringa leaf powder and Aloe vera leaf powder) compared to IBA powder and untreated cuttings in a randomised complete block design (RCBD) with four replications. Finally, a field study was performed to investigate the effect of different planting densities and fertiliser types on the leaf biomass and phytonutrient content. The study was set up in a two factorial RCBD with three plant densities (20 cm x 20 cm, 30 cm x 30 cm and 40 cm x 40 cm) and three fertiliser sources (poultry manure, biochar, and inorganic fertiliser) with 3 replications. Results indicated that primed seeds accelerated germination speed regardless of priming agents. Hydropriming of 4 hours was the best for Moringa germination percentage and germination index, which increased most growth parameters and vigour index and grew best in topsoil: coir dust: peat (5:2:1) media, hence suggested for Moringa seedling production. The results further indicated that multiplication of the Moringa tree could be achieved without bio-stimulant application using a cutting diameter of 40 mm planted in growing media of topsoil: coir dust: peat (5:2:1) with a higher survival rate and better shoots and root growth. The ideal plant density was 30 cm x 30 cm, with 20.4 Mg ha-1 dry matter, which was at par with 20.5 Mg ha−1 in 20 cm x 20 cm density in the respective year. The application of inorganic fertiliser resulted in a higher dry matter yield. However, poultry manure application had the highest crude protein, nitrogen, calcium and zinc. Therefore, the use of poultry manure as a fertiliser is recommended to improve nutritional quality, reduce environmental and health risks, and be less expensive for smallholder growers.